Assessing the Feasibility of Work From Anywhere (WFA) for Local Government Civil Servants in Indonesia: Ergonomic Risk Implications - Nangameka, Teresa I; Meiyenti, Ira; Caturani, Citra; Ginting, Yoga Hananta (AIBPM Publisher, 2025)
This study analyzes the feasibility of implementing Work From Anywhere (WFA) for local government Civil Servants (ASN) in Indonesia by placing ergonomic risk as a mediating variable. Changes in the work landscape due to the COVID-19 pandemic have encouraged the adoption of flexible work models. Still, its implementation in the Indonesian public sector faces structural, cultural, and health risk challenges that have not been comprehensively studied. Using a quantitative explanatory approach, data were collected from 177 ASN respondents with prior Work From Home (WFH) experience during the pandemic, providing a relevant empirical basis for evaluating WFA. Data were collected through an online questionnaire based on a Likert scale, covering five main variables: supporting infrastructure, digital competence, organizational support, ergonomic risk, and perception of WFA feasibility. The analysis was conducted using Structural Equation Modeling (SEM) to test the five hypotheses proposed, including the mediating effect of ergonomic risk. The results show that supporting infrastructure and organizational support have a significant positive effect on the perception of WFA feasibility. In contrast, digital competence and ergonomic risk do not significantly influence WFA feasibility